Synthesis of Titanium Aluminide Based Compounds and Composites with Nanocrystalline and Bimodal Structures - O. N. Senkov; N. Srisukhumbowornchai; F. H. Froes (The Minerals, Metals and Materials Society, 1998)
"Mechanical alloying (MA) and thermohydrogen processing (THP) approaches were used to synthesize amorphous or nanocrystalline powders of the titanium-aluminide-based alloys and composites. Fully dense samples with nanocrystalline and bimodal structures were produced from these powders by hot isostatic pressing. The stability of the microstructures during continuous heating at high temperatures was studied. Characterization techniques including X-ray diffraction, scanning and transmission electron microscopy, energy dispersive spectroscopy, and differential thermal analysis were used in this work.IntroductionAs performance demands increase, so do the demands for enhanced mechanical property combinations at reduced overall weight; and reduced weight can most efficiently be realized by the use of low-density metals with high specific strength, such as titanium alloys and titanium-aluminum intermetallics [l]. The TiAl-based alloys are attractive for high temperature applications, however, they exhibit poor ambient temperature ductility and fracture toughness [2-4]. Incremental improvements can be obtained using ingot metallurgy processing [1,2] but more substantial developments require ""far from equilibrium"" (FFE) synthesis [5-8] which allows development of novel constitutional and microstructural effects, leading to enhanced physical and mechanical properties. Improved ductility of titanium aluminide intermetallics can be achieved by disordering, grain refinement and deoxidation of the matrix, while good elevated temperature properties are achieved due to a dispersion of fine, thermodynamically stable, second phase particles.The approaches for producing nanocrystalline and amorphous TiAl-based alloys and composites used in this work included FFE powder metallurgy techniques such as rapid solidification, mechanical alloying and thermohydrogen processing. The rapid solidification (RS) technique allows extension of solubility limits, production of novel phases, and much more refined microstructures (down to nanostructure or even amorphous range) than is possible using the ingot metallurgy technique [9]. Mechanical alloying (MA) is a process in which heavy working of powder particles results in intimate alloying by repeated deformation, fracturing and welding. This process can produce greater departure from FFE than RS, leading to greater refinement effects; and additionally allows production of a dispersion of second phase particles [10]. Thermohydrogen processing involves hydrogen as a temporary alloying element in titanium to facilitate processes, refine microstructure, and improve final mechanical properties [11]; it was used in the present work to improve MA process. The combination of these three processes was expected to control the final microstructure even better than either process used alone."